Promoting Success and Well-Being Through a Chair Support Group - Grace A. Mims Ph.D.; Kenneth E. Anderson Ph.D.; Richard C. Meyer Ed.D.; Nita Unruh Ed.D. (Academic Chairpersons Conference Proceedings, 2015)
Department chairs are often exposed to occupational stressors that may lead to burnout. The presenters will discuss a chair support group they developed to provide one another support, insight, perspective, collaboration, advocacy, and resources. Implementation strategies for a variety of initiatives will be offered.
Keywords: burnout prevention; support group; self-care; organizational culture; chair collaboration